Pengaruh Model Project Based Learning Berbantuan Media Gambar Berseri terhadap Keterampilan Menulis Teks Eksplanasi Siswa Kelas VIII SMP Negeri 27 Padang - Rozika, Alya; R, Syahrul (Journal of Education Language and Innovation, 2024)
This research is motivated by the low skill in writing explanatory texts of grade VIII students of SMP Negeri 27 Padang, which is caused by low interest in learning, lack of understanding of the material, and lack of motivation and variety of learning models. Therefore, an effective learning approach is needed to improve student learning outcomes in writing explanatory texts. This study aims to describe students' explanatory text writing skills before and after using the project-based learning model assisted by serial image media and measure the influence of the model on students' writing skills. The method used in this study is an experimental method with a quantitative design. The data was analyzed using a percentage formula, a calculated average, a data analysis requirement test, and a t-test. The study results show that applying the project-based learning model assisted by serial image media positively impacts students' explanatory text-writing skills. This study concludes that using appropriate learning models and media can significantly improve students' writing skills and encourage their creativity and interest in learning.